Flobsion: Flexible option with benefit sharing - Nikolay Khabarov; Ruben N. Lubowski; Andrey Krasovskii; Michael Obersteiner (International Journal of Financial Studies, 2019)
Global environmental goals and the Paris agreement declared the need to avoid dangerous climate change by reducing emissions of greenhouse gases with an ultimate goal to transform today's policies and reach climate neutrality before the end of the century. In the medium to long-term, climate policies imply rising CO 2 price and consequent financial risk for carbon-intensive producers. In this context, there is a need for tools to buffer CO 2 prices within the period of transition to greener technologies when the emission offsetting markets expose high volatility. Contracts for optional future purchase of carbon credits could provide emitters with a cost-efficient solution to address existing regulatory risks. At the same time, this would help to create much needed financing for the projects generating carbon credits in the future. This work presents the concept of a flobsion-a flexible option with benefit sharing-and demonstrates its advantages in terms of risk reduction for both seller and buyer as compared to both a 'do nothing' strategy (offsetting at future market price) and a traditional option with a fixed strike price. The results are supported analytically and numerically, employing as a benchmark the dataset on historical CO 2 prices from the European Emission Trading Scheme. Flobsion has the potential to extend the traditional option in financial applications beyond compliance markets.
Keywords: 330; CO2; emissions offsetting; options; financial risk; benefit sharing; climate policy